Intracellular virion traffic to the endosome driven by cell type specific sialic acid receptors determines parvovirus tropism - Calvo-López, Tania; Grueso, Esther; Sánchez-Martínez, Cristina; Almendral, José M. (Frontiers in Microbiology, 2023)
Parvoviruses are promising anticancer and gene therapy agents, but a deep knowledge of the entry process is crucial to exploit their therapeutic potential. We addressed this issue while attempting to re-target the oncolytic parvovirus Minute Virus of Mice (MVMp) to the tumor vasculature. Residues at three functional domains of the icosahedral capsid were substituted by rational design with peptides competing the vascular endothelial growth factor. Most substitutions impaired virus maturation, though some yielded infectious chimeric virions, and substitutions in a dimple at the twofold axis that allocates sialic acid (sia) receptors altered viral tropism. One dimple-modified chimeric virion efficiently attached as MVMp to 2-linked sia moieties, but infection was impaired by the binding to some inhibitory 2-3,-6,-8 sia pseudoreceptors, which hampers intracellular virus traffic to the endosome in a cell type dependent manner. Infectious from non-productive traffic could be mechanistically discriminated by an endosomal drastic capsid structural transition comprising the cleavage of some VP2-Nt sequences and its associated VP1-Nt exposure. Correspondingly, neuraminidase removal of inhibitory sia moieties enhanced infection quantitatively correlating to the restored virus traffic to the endosome and the extent of VP2-Nt cleavage/VP1-Nt exposure. This study illustrates (i) structural constrains to re-target parvoviruses with evolutionary adopted narrow grooves allocating small sia receptors, (ii) the possibility to enhance parvovirus oncolysis by relaxing the glycan network on cancer cells surface, and (iii) the major role played by the attachment to cell type specific sias in the intracellular virus traffic to the endosome, which may determine parvovirus tropism and host range.